Landscape approaches for the 30x30 target: Potential applications and practical recommendations - Paulina G. Karim; Kuang-Chung Lee (Parks)
Landscape approaches have been recognised as an effective solution for reconciling conservation and developmental demands at local scales. Though suitable in various contexts of human-nature interactions, their application is increasingly considered in relation to area-based conservation. Target 3 (30x30 Target) of the Kunming-Montreal Global Biodiversity Framework (KM-GBF) specifically calls for protected areas, other effective area-based conservation measures (OECMs) and Indigenous and traditional territories to be 'integrated into wider landscapes and seascapes and the ocean'. This short communication pursues three objectives. First, we suggest various areabased conservation settings where a landscape approach can be applied. Second, we discuss how characteristic features and strengths of landscape approaches can be leveraged to support Target 3. Lastly, we provide practical recommendations for enabling their effective operationalisation.